Lymphocyte Doubling Time As A Key Prognostic Factor To Predict Time To First Treatment In Early-Stage Chronic Lymphocytic Leukemia - Morabito, Fortunato; Tripepi, Giovanni; Moia, Riccardo; Recchia, Anna Grazia; Boggione, Paola; Mauro, Francesca Romana; Bossio, Sabrina; D’Arrigo, Graziella; Martino, Enrica Antonia; Vigna, Ernesto; Storino, Francesca; Fronza, Gilberto; et al. (Frontiers in Oncology, 2021)
The prognostic role of lymphocyte doubling time (LDT) in chronic lymphocytic leukemia (CLL) was recognized more than three decades ago when the neoplastic clone's biology was almost unknown. LDT was defined as the time needed for the peripheral blood lymphocyte count to double the of the initial observed value. Herein, the LDT prognostic value for time to first treatment (TTFT) was explored in our prospective O-CLL cohort and validated in in two additional CLL cohorts. Specifically, newly diagnosed Binet stage A CLL patients from 40 Italian Institutions, representative of the whole country, were prospectively enrolled into the O-CLL1-GISL protocol (clinicaltrial.gov identifier: NCT00917540). Two independent cohorts of newly diagnosed CLL patients recruited respectively at the Division of Hematology in Novara, Italy, and at the Hospital Clinic in Barcelona, Spain, were utilized as validation cohorts. In the training cohort, TTFT of patients with LDT >12 months was significantly longer related to those with a shorter LDT. At Cox multivariate regression model, LDT<12 months maintained a significant independent relationship with shorter TTFT along with IGH unmutated (IGHVumut) status, 11q and 17p deletions, elevated b2M, Rai stage I-II, and NOTCH1 mutations. Based on these statistics, two regression models were constructed including the same prognostic factors with or without the LDT. The model with the LTD provided a significantly better data fitting (χ2=8.25, P=0.0041). When the patients from the training and the validation sets were considered together, LDT <12 months significantly maintained its negative prognostic power in both the IGHVmut (732 cases, HR=2.7, 95% CI 2.0–3.8, P<0.0001) and IGHVunmut (330 cases, HR=2.6, 95% CI 1.9–3.4, P<0.0001) groups. The risk prediction developed including LDT had better prognostic accuracy than those without LDT. Moreover, the Harrell’C index for the scores including LDT were higher than those without LDT, although the accepted 0.70 threshold exceeded in both cases. These findings were also confirmed when the same analysis was carried out according to TTFT's explained variation. Overall, in this study, we demonstrated that LDT could be re-utilized together with the more sophisticated prognostic factors to manage the follow-up plans for Binet stage A CLL patients.